International Architecture News (project baikal, 2023)
The news announces the 28th World Congress of Architects and the 6th Edition of the Baku International Architecture Award. It presents the results of the Golden Cubes Awards, the International Innovative Health Design Awards and the Competition for the Requalification of Byrsa Acropolis and Rehabilitation of the Carthage National Museum in Tunisia.
Keywords: International Union of Architects; award; international competition